Now the Sun Sinks in the Sea: The Sacred Works of Þorkell Sigurbjörnsson - Kristín Jónína Taylor (Athens Journal of Humanities & Arts, 2022)
Þorkell Sigurbjörnsson’s contributions to Icelandic music were manifold, encompassing teaching, composition, arts administration, music criticism, radio program hosting, solo and chamber performance, conducting, and countless other accomplishments. He remains the most prolific of all Icelandic composers with over 350 compositions. Those works for which Þorkell is best known are his exquisite sacred works, of which there are at least fifty. For that reason, this paper will focus on Þorkell’s sacred works and the diversity of approaches he utilized. Þorkell had familial connections with the Iceland Lutheran Church. A number of his compositions were settings of his father's poetry, including the hymn Nú hverfur sól í haf. The most notable and famous of his hymns is Heyr, himna smiður, a setting of a 13th century hymn text by Kolbeinn Tumason. Other prominent works include several choral settings of Psalms of David, a Missa Brevis, and the oratorio Immanúel, which was based on text by Þorkell’s brother Bishop Karl Sigurbjörnsson. The sacred works Þorkell wrote are not restricted to choral compositions, as there are several instrumental works (including Blessed Be the Feet of the Peacemaker for organ pedals).